2017
DOI: 10.1111/mcn.12522
|View full text |Cite
|
Sign up to set email alerts
|

Yogurt consumption during pregnancy and preterm delivery in Mexican women: A prospective analysis of interaction with maternal overweight status

Abstract: Preterm delivery is an important cause of perinatal morbidity and mortality, often precipitated by maternal infection or inflammation. Probiotic-containing foods, such as yogurt, may reduce systemic inflammatory responses. We sought to evaluate whether yogurt consumption during pregnancy is associated with decreased preterm delivery. We studied 965 women enrolled at midpregnancy into a clinical trial of prenatal docosahexaenoic acid supplementation in Mexico. Yogurt consumption during the previous 3 months was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…The effects of probiotic yogurt were also evaluated in reference to the treatment of bacterial vaginosis and preventing preterm labor, as 30%-50% of preterm births are thought to be from maternal infection [20,21]. While the current mechanism of action is largely unknown, probiotics have been shown to be a viable alternative to antibiotics for bacterial vaginosis in pregnancy through the displacement of pathogens and interference of the inflammatory immune cascade [14,21]. Nonetheless, conflicting studies have also emerged in which research showing improved bowel performance is pitted against minimal changes in maternal microbiomes [6,15].…”
Section: Review Of Studiesmentioning
confidence: 99%
“…The effects of probiotic yogurt were also evaluated in reference to the treatment of bacterial vaginosis and preventing preterm labor, as 30%-50% of preterm births are thought to be from maternal infection [20,21]. While the current mechanism of action is largely unknown, probiotics have been shown to be a viable alternative to antibiotics for bacterial vaginosis in pregnancy through the displacement of pathogens and interference of the inflammatory immune cascade [14,21]. Nonetheless, conflicting studies have also emerged in which research showing improved bowel performance is pitted against minimal changes in maternal microbiomes [6,15].…”
Section: Review Of Studiesmentioning
confidence: 99%
“…Furthermore, infection is an important factor in pre-term labor and pathogenic microbes can be outcompeted by probiotics, yet, according to a systematic review by Jarde et al (101) probiotics neither increased nor decreased pre-term birth (101). Kriss et al (102) corroborates this conclusion, but suggests that high probiotic yogurt consumption may be associated with reduction in preterm delivery in Mexican women of normal weight as opposed to overweight (102). Altogether, limited evidence exists that maternal probiotics beneficially impact the mother-infant interface and more research is needed on how changes in the gut microbiota that occur during pregnancy might be modulated by probiotic treatment.…”
Section: Maternal Probioticsmentioning
confidence: 88%
“…In 2007, the Cochrane Database demonstrated that the use of probiotics effectively reduced bacterial vaginosis during pregnancy [29]. A Mexican group reported that non-overweight women who ate more than 5 cups of yogurt per week had a reduced risk of PTB [11]. In our study, consumption of yogurt > 5 times/week before pregnancy was found to be associated with a reduced risk of early PTB (< 34 weeks) but not overall PTB or late PTB.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the risk of PTB based on the intake of each fermented food, we categorized participant responses for consumption of each food type as follows: miso soup, 1–2 days/week, 3–4 days/week, or ≥ 5 days/week and yogurt, < once per week, 1–4 times/week, or ≥ 5 times/week according to previous research [11]. The consumption of cheese and fermented soybeans was categorized as < once/week, 1–2 times/week, or ≥ 3 times/week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation